1988
DOI: 10.1177/107906328800100206
|View full text |Cite
|
Sign up to set email alerts
|

The Sex Killer

Abstract: Thirteen sex killers were compared to 13 nonsex killers and 13 nonhomicidal sexually aggressive men on sexual history, substance abuse, history of violence, mental illness and personality, brain pathology and endocrine abnormalities.There were more similarities among the three groups than differences. Among the findings, the presence of transvestism and the early appearance of sadism differentiated the sex killers from the other two groups. Sex killers also killed by strangulation more often than nonsex killer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
2
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(127 citation statements)
references
References 32 publications
9
114
2
2
Order By: Relevance
“…In general the results of the present investigation are consistent with the speculations concerning the role of deviant sexual arousal with homicidal sex offenders (11)(12)(13)(14)(15). They also support the contention that phallometric assessment is a useful tool in work with men who are sexually attracted to children (18)(19)(20).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In general the results of the present investigation are consistent with the speculations concerning the role of deviant sexual arousal with homicidal sex offenders (11)(12)(13)(14)(15). They also support the contention that phallometric assessment is a useful tool in work with men who are sexually attracted to children (18)(19)(20).…”
Section: Discussionsupporting
confidence: 90%
“…It has been suggested that many HSOs focus on sexually sadistic acts to achieve arousal, and that this may be their major distinguishing feature (11)(12)(13)(14). In support of this contention, one study found that HSOs showed the greatest deviant phallometric responses to sadistic stimuli compared to nonsexual murderers and nonhomicidal SOs (14). Consistent findings come from our clinic in which we compared incest offenders and a mixed group of HSOs (i.e.…”
Section: Hcms Cms and Controls Firestone Bradford Greenberg Andsupporting
confidence: 73%
See 1 more Smart Citation
“…Bei Sexualstraftätern, die ihre Opfer töten, ließen sich mit 52-82 % signifikant häufiger paraphile Störungen diagnostizieren als bei Sexualstraftätern, die dies nicht tun (24-43 %), wobei die häufigsten paraphilen Störungen von Sexualmördern sexueller Sadismus und Pädophilie waren (Briken et al 2006;Firestone et al 1998aFirestone et al , 1998bKoch et al 2011;Langevin et al 1988). In einer kanadischen Studie erfüllten Sexualmörder im Vergleich zu Sexualstraftätern, die ihre Opfer nicht töteten, signifikant häufiger die Diagnosekriterien von Exhibitionismus, Fetischismus, Frotteurismus, homosexueller Pädophilie und sexuellem Masochismus (Chan und Beauregard 2016).…”
Section: Paraphile Störungen Und Sexualdelinquenzunclassified
“…Bei Sexualstraftätern, die ihre Opfer töten, wurde mit Raten zwischen 52 und 83 % eine deutlich höhere Prävalenz an Persönlichkeitsstörungen beschrieben als bei Sexualstraftätern, die ihre Opfer nicht töten (4-58 %). Dabei waren antisoziale Persönlichkeitsstörungen bei Sexualmördern signifikant häufiger anzutreffen als bei Sexualstraftätern, die ihre Opfer nicht töten (Firestone et al 1998a(Firestone et al , 1998bKoch et al 2011;Langevin et al 1988;Oliver et al 2007). Insbesondere Störungen aus den Clustern A und B sind in der Gruppe der Sexualstraftäter mit Tötungsdelikten überrepräsentiert (Chan et al 2015;Chan und Heide 2009;Hill et al 2006;Chan und Beauregard 2016).…”
Section: Persönlichkeitsauffälligkeitenunclassified